I Won’t Give you a Story of Suffering: Queer Migrants’ Everyday Resistance in İstanbul - Aytaçoğlu, Öykü; Pica, Cosimo (PARTECIPAZIONE E CONFLITTO, 2025)
This article explores how queer migrants’ experiences reveal the complex dynamics of sexual and gender-based violence (SGBV) and everyday resistance. Utilising a socio-anthropological and geographical approach, it examines the intersections of migration, queerness, and resistance in Türkiye - a leading refugee-hosting country with diverse origins driven by various motivations. Focusing on queer migrants who navigate among political and gender boundaries that often homogenise migration narratives, the study draws on ethnographic fieldwork conducted in Türkiye from 2019 to 2024. It highlights the structural violence and oppression shaping their experiences and investigates İstanbul as a potential queer oasis for life experiences that have been positioned on the margins of dominant gender and racial norms. Furthermore, the article examines how vulnerability is transformed into everyday resistance, showcasing diverse narratives that subvert the prevailing portrayal of migrants as solely suffering. Based on firsthand accounts, it illustrates how people endure within heteronormative and oppressive structures through the types of tactics we suggest referring to as evasive, solidarity, belonging and claiming.